Determinants of interbank rate in money market: a comparison between UK and China - Zhang, Jun (2012)
Since 2007, the financial crisis and the credit crunch had a big impact in the global world on the money markets. Most money market rates rose rapidly and became unstable such as London Interbank Offered Rate (LIBOR). Most central banks and governments made some series of monetary policies to control and affect their money market rates. Moreover, a number of papers documented and concluded the close relationship between some monetary factors and money market rates. These factors were used as intermediary instruments by central banks to control and affect money markets. However, there was no analysis about the detailed relationship and strength between them. And there was no comparison about different money markets. Which factors were the efficient instruments to transmit the central banks’ expectations of money market rates was valuable to figure out. In different money markets, those factors were same or different to the money market rates.